Linear Micropolar Elasticity Analysis of Stresses in Bones under Static Loads - Eremeyev, V.A.; Skrzat, A.; Stachowicz, F. (Проблемы прочности, 2017)
We discuss the finite element modeling of porous materials such as bones using the linear micropolar elasticity. In order to solve static boundary-value problems, we developed new finite elements, which capture the micropolar behavior of the material. Developed elements were implemented in the commercial software ABAQUS. The modeling of a femur bone with and without implant under various stages of healing is discussed in details.